2017
DOI: 10.21474/ijar01/2853
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction Among Students of Health Faculties in Jazan University, Ksa.

Abstract: Aim: To determine the extent of internet addiction among students of health faculties in Jazan University and its effects on their academic performance and social relationships. Method: This study reports the results of surveyinvolved 400 students (198 males 202 females) from 4 health faculties in Jazan University to measure the prevalence of internet addiction among the students and its effects on the academic performance and social relationships. It is a cross sectional study in which a standardized self-adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…One of such studies showed that 3 out of a cohort of 161 students at King Abdul-Aziz University, Jeddah, Saudi Arabia were addicted to the internet while another cross-sectional study in Jazan revealed 58.8% of the medical student to be mildly addicted to the internet. [ 14 15 ] This is important because academic performance is positively correlated to the quality of life among students. [ 16 ] The aim of this study is to estimate the prevalence of internet addiction among medical students at King Saud University and to measure the association between internet addiction and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…One of such studies showed that 3 out of a cohort of 161 students at King Abdul-Aziz University, Jeddah, Saudi Arabia were addicted to the internet while another cross-sectional study in Jazan revealed 58.8% of the medical student to be mildly addicted to the internet. [ 14 15 ] This is important because academic performance is positively correlated to the quality of life among students. [ 16 ] The aim of this study is to estimate the prevalence of internet addiction among medical students at King Saud University and to measure the association between internet addiction and quality of life.…”
Section: Introductionmentioning
confidence: 99%